Debtor Liability for Non-Performance of a Homologated Composition Agreement: Analysis Of Central Jakarta Commercial Court Decision No. 31/Pdt.Sus-Pembatalan Perdamaian/2023 - Syarifah Bilqis Rasyida Harahap; Puspa Melati Hasibuan; Zulfi Chairi (Global Journal of Law, AI & Ethics, 2026)
This study examines the legal standard for debtor liability when a homologated composition agreement is not performed and clarifies the procedural steps that must precede bankruptcy under Indonesian bankruptcy law. The research uses a normative doctrinal method with statute, case, and conceptual approaches. Primary legal materials include Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU), the homologation decision in Case No. 78/Pdt.Sus-PKPU/2019/PN.Niaga.Jkt.Pst, Central Jakarta Commercial Court Decision No. 31/Pdt.Sus-Pembatalan Perdamaian/2023/PN Niaga.Jkt.Pst, and Supreme Court Decision No. 186 K/Pdt.Sus-Pailit/2024. The study finds that debtor non-performance does not automatically produce bankruptcy. Under Articles 170, 171, and 291, a creditor must seek cancellation, the debtor bears the burden of proving performance, and the court may grant a maximum thirty-day period to cure the default before deciding whether cancellation is justified. In the case studied, PT Oilrig Binamas Pratama had paid an initial IDR 1 billion but failed to pay the remaining IDR 6.114 billion due by 27 July 2020. After repeated demands in May 2023, the debtors submitted no evidence of performance, relied on an unsubstantiated asset-sale proposal, and later offered a post-dated cheque. The Commercial Court treated these circumstances as sufficient proof of neglect and cancelled the composition agreement; the Supreme Court subsequently upheld the decision. The article contributes an operational framework for assessing material non-performance and good faith based on maturity, duration and magnitude of default, repeated demands, evidentiary proof, and the credibility of a proposed cure, thereby balancing business rescue with creditor protection